Original papersPrevalence of atopic dermatitis in infants during the first six months of life: authors’ observations - Kamer, Barbara; Pasowska, Renata; Dółka, Elżbieta; Blomberg, Agnieszka; Rotsztejn, Helena (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2013)
Introduction : Atopic dermatitis (AD) is a frequent chronic skin disease in infants. It creates great difficulties, both diagnostic and therapeutic. Aim: To assess the prevalence of atopic dermatitis in infants during the first 6 months of life. Material and methods: The analysis comprised 2256 children at the age of not more than 6 months, treated at the 2 nd Department of Paediatrics and Allergology of the Polish Mother’s Memorial Hospital in Lodz, Poland, during seven years. Out of all the patients, children with cutaneous changes were isolated, and the location, type and aetiology of changes were assessed. Results: Dermal changes were diagnosed in 471 children, including 391 (17.3% of all the patients) with atopic dermatitis. Out of the children with AD, IgE-dependent allergy was identified in 39.9%. Cow’s milk protein was the most frequent sensitising allergen. In 71.6% of the infants, cutaneous changes were disseminated and involved at least two areas of the body. All of them were strongly itching. An applied elimination diet, together with anti-allergic medications in some of the children, provided a clear clinical improvement. Conclusions : Performed studies demonstrated the prevalence of atopic dermatitis in 17.3% of examined children. The changes in children with AD were disseminated, what was confirmed already at the infantile age. The obtained clinical improvement after the applied therapy indicates a relationship between the observed symptoms and allergic disease.